2016
DOI: 10.1007/s00127-016-1280-x
|View full text |Cite
|
Sign up to set email alerts
|

Violent typologies among women inpatients with severe mental illness

Abstract: PurposeExtant severe mental illness (SMI) and physical violence literature focus disproportionately on community-based men samples. To address this empirical imbalance, the current study explored violence towards others and oneself among women inpatients with SMI. As those with SMI are more likely to be victims than perpetrators of violence, victimisation was also an important factor assessed in this study.MethodsThe study used a quantitative within-subject cross-sectional design. Data were extracted from 5675… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…These findings were consistent with an Indian study, which reported that patients with schizophrenia committed 60.8% to 77.4% of assaults. [ 14 ] Another study reported that patients diagnosed with psychotic disorders such as schizophrenia,[ 20 ] bipolar disorders in combination with cannabis and other substance abuse,[ 21 ] and one systematic review stated, a psychotic disorder (or schizophrenia), a manic episode or bipolar disorder, and personality disorder were at increased risk of becoming aggressive in the psychiatric ward. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent with an Indian study, which reported that patients with schizophrenia committed 60.8% to 77.4% of assaults. [ 14 ] Another study reported that patients diagnosed with psychotic disorders such as schizophrenia,[ 20 ] bipolar disorders in combination with cannabis and other substance abuse,[ 21 ] and one systematic review stated, a psychotic disorder (or schizophrenia), a manic episode or bipolar disorder, and personality disorder were at increased risk of becoming aggressive in the psychiatric ward. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…These are forms of mental illness that cause considerable disruption to one's life, affecting a person's ability to obtain stable employment, maintain adequate socioeconomic status (Topor, Ljungqvist & Strandberg, 2016), and social relationships (Prince et al, 2018), and that which increases the risk for poor physical health outcomes (Blomqvist et al, 2018). In keeping with the classification of severe mental illness used by Schaefer, Broadbent, and Bruce (2016), severe mental illness can be divided into two categories of disorder, psychotic (ex. schizophrenia) and non-psychotic (ex.…”
Section: Sampling Inclusion and Exclusion Criteriamentioning
confidence: 99%